A fate worse than death : Indian captivities in the West, 1830-1885 - Michno, Gregory, 1948- (Caxton Press, 2007)
Captivity narratives have been a standard genre of writings about Indians of the East for several centuries. Until now, the West has been almost entirely neglected. Now Gregory and Susan Michno have rectified that with this painstakenly researched collection of vivid and often brutal accounts of what happened to those men and women and children that were captured by marauding Indians during the settlement of the West.